2018
DOI: 10.1016/j.immuni.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptor Protein CARD9 Protects against Colon Cancer by Restricting Mycobiota-Mediated Expansion of Myeloid-Derived Suppressor Cells

Abstract: The adaptor protein CARD9 links detection of fungi by surface receptors to the activation of the NF-κB pathway. Mice deficient in CARD9 exhibit dysbiosis and are more susceptible to colitis. Here we examined the impact of Card9 deficiency in the development of colitis-associated colon cancer (CAC). Treatment of Card9 mice with AOM-DSS resulted in increased tumor loads as compared to WT mice and in the accumulation of myeloid-derived suppressor cells (MDSCs) in tumor tissue. The impaired fungicidal functions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
160
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(173 citation statements)
references
References 60 publications
10
160
3
Order By: Relevance
“…demonstrate that CARD9 promotes sex‐biased colon tumors in the adenomatous polyposis coli multiple intestinal neoplasia (APC min ) mouse model. Our recently study on colitis‐associated colon cancer confirms a critical role of CARD9 in colon cancer . We found that CARD9 −/− mice are more susceptible to colitis‐associated cancer and outline a mechanism whereby fungal dysbiosis increases the frequency of MDSCs.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…demonstrate that CARD9 promotes sex‐biased colon tumors in the adenomatous polyposis coli multiple intestinal neoplasia (APC min ) mouse model. Our recently study on colitis‐associated colon cancer confirms a critical role of CARD9 in colon cancer . We found that CARD9 −/− mice are more susceptible to colitis‐associated cancer and outline a mechanism whereby fungal dysbiosis increases the frequency of MDSCs.…”
Section: Discussionsupporting
confidence: 70%
“…Our recently study on colitis-associated colon cancer confirms a critical role of CARD9 in colon cancer. 6 We found that CARD9 −/− mice are more susceptible to colitis-associated cancer and outline a mechanism whereby fungal dysbiosis increases the frequency of MDSCs. In our study, we found that supernatant from tumor cells can also differentiate MDSCs from BM cells, providing another regulatory way for MDSCs.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Like bacteria, fungi are a component of the microbiota at barrier surfaces in mammals, where emerging studies suggest they play an important role in shaping host immunity and tissue homeostasis (Belkaid and Harrison, 2017;Iliev and Leonardi, 2017). Alterations in intestinal fungal composition and dysbiosis have been associated with human inflammatory disorders, such as inflammatory bowel disease (IBD), colorectal cancer, and allergy (Sokol et al, 2017;Wypych and Marsland, 2018;Coker et al, 2019), in which mutations or deficiencies in fungal recognition receptors or downstream signaling pathways have been shown to substantially influence disease severity (Iliev et al, 2012;Wang et al, 2016Wang et al, , 2018Li et al, 2018;Malik et al, 2018). Nevertheless, how fungi interact with the mammalian host and the molecular mechanisms mediating fungal recognition and resultant host responses remains incompletely defined.…”
Section: Introductionmentioning
confidence: 99%